2014
DOI: 10.5935/1984-6835.20140109
|View full text |Cite
|
Sign up to set email alerts
|

Method for Sediment Texture Characterization Using Spectroscopy Techniques and Multivariate Analysis

Abstract: Resumo: O objetivo deste estudo foi apresentar um método para caracterização da textura de sedimentos combinando três técnicas espectroscópicas com analise multivariada. Em particular, foram utilizados dados de medidas de espectroscopia de absorção atômica de chama (FAAS), fluorescência de raios X por dispersão em energia (EDXRF) e espectroscopia fotoacústica (PAS) em amostras de sedimento superficial de lago, os quais foram combinados com o método de análise de componentes principais para a analise exploratór… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…Analysis of mineral content in sediment was done according to Melquiades et al [ 15 ]. By weighing 0.5 g of dry sample (3 replicates for each), digesting with 15 ml 30% HNO 3 , placing on hot plate at 80°C to accelerate the reaction for 4 h. The samples were then added with 18 ml 30% H 2 O 2 and continued heating for 2 h to digest the organic matter (probably added some distilled water to prevent drying out).…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of mineral content in sediment was done according to Melquiades et al [ 15 ]. By weighing 0.5 g of dry sample (3 replicates for each), digesting with 15 ml 30% HNO 3 , placing on hot plate at 80°C to accelerate the reaction for 4 h. The samples were then added with 18 ml 30% H 2 O 2 and continued heating for 2 h to digest the organic matter (probably added some distilled water to prevent drying out).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Capra et al, (2015) suggested the use of sediment for fertilization. Sediment texture is the measure of the number of particles (clay, sand and silt) found in the sediment component (Melquiades et al, 2014). Physical content of the sediment is influence by the kind of particles in the chemical structure (Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical analysis of the sediment not just for the nature of the sediment, also to understand the physical properties of the sediments and revealed the relationship and the effect of the grain size, source materials and depositional environment. Some investigations have shown the dependence of radionuclide concentrations, heavy metal, and magnetic susceptibility on grain size (Ramasamy et al 2014;Paramasivam et al 2015;Melquiades et al 2014).…”
Section: Introductionmentioning
confidence: 99%